Effect of Point Angle on Delamination in Drilling of KFRP Composite - Mohammad Muslimin Ilham; Am. Mufarrih (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) - ITP, 2018)
Drilling is the most important machining process in the automotive and manufacturing industries. The performance of drilling KFRP composite materials can be measured by quality characteristics such as surface roughness, burr height, roundness, power consumption, thrust force and delamination. This study aims to determine the effect of process variable variation to delamination response. The experimental is held with three replication. The variations of drilling process variable is point angle (90°, 100°, 110°, 118°, 130° and 140°). The response variables observed is delamination. The cutting tool used is the twist drill HSS Nachi. One Way ANOVA is used to determine the process variables that have a significant influence on the observed response variables. The results showed that the point angle had a significant effect on response of delamination. Increasing the point angle will increase the delamination.